Usulan Penerapan Keselamatan Kerja Dengan Menggunakan Metode Fault Tree Analysis (FTA) : Studi Kasus: PT. Sipatex Putri Lestri - Ujang Cahyadi; Dedi Sa'dudin Taptajani; Sindi Oktaviany (Jurnal Kalibrasi, 2026)
PT Sipatex Putri Lestari is a company engaged in weaving, printing, dyeing, texturizing, and yarn dyeing. The company has not yet formally implemented an Occupational Safety and Health Management System (SMK3), which has led to various issues, particularly in the printing division. A prominent issue is the high rate of workplace accidents, occupational illnesses caused by the work environment, and the negative environmental impact of industrial activities. These problems highlight the urgent need for the implementation of Occupational Safety and Health (OSH) measures as a risk mitigation strategy. This study aims to analyze the rate of workplace accidents, the severity of these accidents, and to identify the main contributing factors to workplace accidents at PT Sipatex Putri Lestari. The method used is Fault Tree Analysis (FTA), which helps reveal the root causes of accidents and provides recommendations as the basis for implementing an OSH system.Data analysis from 2021 to 2023 shows an increasing number of workplace accidents in the printing division, with 3, 4, and 6 incidents per year, respectively. The accident frequency rates recorded were 9.65 in 2021, 12.87 in 2022, and 19.30 in 2023, while the severity rates were 157.65, 292.79, and 585.58, respectively. The Total Safe (T Selamat) value also showed a significant increase, from 585.4 in 2022 to 1004.6 in 2023. This data indicates that workplace accidents at PT Sipatex Putri Lestari have been rising each year, making the implementation of OSH practices an urgent necessity to minimize risks and support the sustainability of the company’s operations.